Identification of putative insect brush border membrane-binding molecules specific to Bacillus thuringiensis delta-endotoxin by protein blot analysis. - Garczynski, S F (1991)
Binding sites for insecticidal toxins of Bacillus thuringiensis are located in the brush border membranes of insect midguts. Two approaches were used to investigate the interactions of B. thuringiensis subsp. kurstaki HD-73 CryIA(c) toxin with brush border membrane vesicles from sensitive and naturally resistant insects: 125I-toxin-vesicle binding assays and protein blots probed with 125I-CryIA(c) toxin. In bioassays, Manduca sexta and Heliothis virescens larvae were highly sensitive, Helicoverpa zea larvae were moderately sensitive, and Spodoptera frugiperda larvae were resistant to CryIA(c) toxin. Studies of binding of 125I-CryIA(c) toxin to brush border membrane vesicles from the larval midguts revealed that all insects tested had high-affinity, saturable binding sites. Significantly, S. frugiperda larvae bind but are not killed by CryIA(c) toxin. Labeled CryIA(c) toxin incubated with protein blots identifies a major binding molecule of 120 kDa for M. sexta and 148 kDa for S. frugiperda. H. virescens and H. zea are more complex, containing 155-, 120-, 103-, 90-, and 63-kDa proteins as putative toxin-binding molecules. H. virescens also contains a minor toxin-binding protein of 81 kDa. These experiments provide information that can be applied toward a more detailed characterization of B. thuringiensis toxin-binding proteins.